2020
DOI: 10.1002/cbin.11357
|View full text |Cite
|
Sign up to set email alerts
|

Critical roles of tyrosyl‐DNA phosphodiesterases in cell tolerance to carnosol‐induced DNA damage

Abstract: Carnosol is a natural compound with pharmacological action due to its anti‐cancer properties. However, the precise mechanism for its anti‐carcinogenic effect remains elusive. In this study, we used lymphoblastoid TK6 cell lines to identify the DNA damage and repair mechanisms of carnosol. Our results showed that carnosol induced DNA double‐strand breaks (DSBs). We also found that cells lacking tyrosyl‐DNA phosphodiesterase 1 (TDP1), an enzyme related to topoisomerase 1 (TOP1), and tyrosyl‐DNA phosphodiesterase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Interestingly, carnosol has also been described as one of the compounds with the best induction of HO-1/low cytotoxicity profile in BV2 microglial cells in vitro (121). Nevertheless, a recent study has indicated that carnosol induces DNA damage, although this activity is associated with abnormal topoisomerase activity in lymphoblastoid TK6 cells (122). Importantly, these compounds have the lowest cytotoxicity when compared to other compounds such as allyl isothiocyanate (ITC) or caffeic acid phenethyl ester (CAPE) (121).…”
Section: Carnosic Acid and Carnosolmentioning
confidence: 99%
“…Interestingly, carnosol has also been described as one of the compounds with the best induction of HO-1/low cytotoxicity profile in BV2 microglial cells in vitro (121). Nevertheless, a recent study has indicated that carnosol induces DNA damage, although this activity is associated with abnormal topoisomerase activity in lymphoblastoid TK6 cells (122). Importantly, these compounds have the lowest cytotoxicity when compared to other compounds such as allyl isothiocyanate (ITC) or caffeic acid phenethyl ester (CAPE) (121).…”
Section: Carnosic Acid and Carnosolmentioning
confidence: 99%
“…Carnosol is a natural compound that has anticancer activity; however, the mechanism of its anticancer effects remains unclear. More recently, carnosol was found to induce the formation of both TOP1cc and TOP2cc (Feng et al 2020). 4-Nitroquinoline-1-oxide (4NQO), a compound that has been shown to be hypersensitive to BLMdeficient cells, induces higher levels of Top1cc formation in BLM-deficient cells than it does in BLM-complemented cells (Miao et al 2006).…”
Section: Topoisomerases and Top Poisonsmentioning
confidence: 99%